Coordination problems triggered by sunspots in the laboratory - Jan Siebert; Guanzhong Yang (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
A sunspot variable is any random variable that is not related to fundamental factors of the economy but a potential coordination device. The coordination power of sunspots has been analysed in theory and in experiments. However, some have discussed whether sunspots, e.g., public announcements such as financial market ratings, can create coordination problems. That discussion reached a new peak during the European sovereign debt crisis. We ask: can a sunspot variable, in form of a random forecast, trigger coordination problems? To answer that, we use a repeated three-player stag hunt game with fixed groups. In our experiment, a sunspot variable points randomly at the risk-dominant or the payoff-dominant choice. We find out-of-equilibrium behaviour caused by the sunspot variable in the short run. In the long run, the sunspot variable can lead to coordination on payoff-dominated equilibria. Only if the sunspot variable points more often to the payoff-dominated alternative, some groups use the sunspot variable consistently as a coordination device. – – Eine Sunspot-Variable ist jede Zufallsvariable, die nicht mit den Fundamentalvariablen einer Volkswirtschaft zusammenhängt, jedoch ein potenzielles Koordinierungshilfsmittel ist. Die Koordinationskraft von Sunspots wurde in der Theorie und in Experimenten umfassend analysiert. Einige diskutierten jedoch, ob Sunspots, z. B. öffentliche Bekanntmachungen wie Finanzmarkt-Ratings, auch Koordinationsprobleme erzeugen können. Diese Diskussion erreichte während der europäischen Staatsschuldenkrise einen neuen Höhepunkt. Wir fragen: Kann eine Sunspot-Variable, in Form einer rein zufälligen Prognose, Koordinierungsprobleme auslösen? Um dies zu beantworten, verwenden wir ein wiederholtes, Dreispieler-Staghuntgame mit festen Gruppen. In unserem Experiment zeigt eine Sunspot-Variable zufällig auf die Risiko-dominante oder die Auszahlungs-dominante Handlungsoption. Wir finden heraus, dass die Sunspot-Variable kurzfristig die Gleichgewichtsfindung erschwert. Langfristig kann die Sunspot-Variable zu einer Koordination auf Auszahlungs-dominierte Gleichgewichte führen. Nur wenn die Sunspot-Variable häufiger auf die Auszahlungs-dominierte Alternative zeigt, nutzen einige Gruppen die Sunspot-Variable konsistent als Koordinierungshilfsmittel.
Keywords: C92; C72; D81; E40; J52; 330; sunspot; coordination; equilibrium selection; correlated equilibria; focal point